Structural Analysis and Validation of a Smart Pantograph Mast Concept. (4th April 2013) - Glisic, Branko; Adriaenssens, Sigrid; Szerzo, Peter
Abstract: To progress the development of deployable, lightweight infrastructure for relief and recovery efforts in the aftermath of natural and man‐made disasters, this article develops a proof of concept for a smart mast that leverages the versatility of pantograph systems and advances in sensor, actuator, and informatics technologies. More specifically the article addresses key design criteria of transportability, deployability, global stability, and site responsiveness through the development of analytical expressions and control framework, and reduced‐scale physical model testing. The case study, a three‐tiered tetrahedral mast is composed of three connected sets of planar pantograph systems and deployed by single actuator located between two of the three mast supports. The article discusses the optimum configurations for the individual design criteria and trade‐offs to be made between compactness, overturning, and operational power. The design, construction, and experimentation with a 73‐cm tall fully deployed physical model reinforce the feasibility of the presented smart mast concept.